2018
DOI: 10.1007/s00204-018-2158-3
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus-induced nephrotoxicity in mice is associated with microRNA deregulation

Abstract: Although Tacrolimus is an immunosuppressive drug widely used in renal transplantation, its chronic use paradoxically induces nephrotoxic effects, in particular renal fibrosis, which is responsible for chronic allograft dysfunction and represents a major prognostic factor of allograft survival. As molecular pathways and mechanisms involved in Tacrolimus-induced fibrogenic response are poorly elucidated, we assessed whether miRNAs are involved in the nephrotoxic effects mediated by Tacrolimus. Treatment of CD-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…In a recent study, Sun et al suggested that the antifibrotic effect of pioglitazone, which is a type of PPARγ agonist, is connected with the modulation of the miR-21-5p/Smad-7 pathway [35]. Tacrolimus-induced nephropathy (which especially manifests as IFTA or glomerular sclerosis) was associated with upregulation of miR-21 in mice renal proximal tubular epithelial cells [36]. Other mechanisms of promoting kidney fibrosis involving miR-21 are also described in the literature [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Sun et al suggested that the antifibrotic effect of pioglitazone, which is a type of PPARγ agonist, is connected with the modulation of the miR-21-5p/Smad-7 pathway [35]. Tacrolimus-induced nephropathy (which especially manifests as IFTA or glomerular sclerosis) was associated with upregulation of miR-21 in mice renal proximal tubular epithelial cells [36]. Other mechanisms of promoting kidney fibrosis involving miR-21 are also described in the literature [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…It is a multifactorial process that begins with acute local inflammation, oxidative stress, renal vasoconstriction, and ends with a chronic fibrogenic response after prolonged FK506 use. 32 Deleteriously, FK506 repeated injection affected renal biomarkers in serum and tissue homogenate ( Table 1 ). The results of this study are consistent with the previous in that FK506-induced nephrotoxicity can be characterized by increased levels of cystatin C and urea ( Figures 4 and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…We downloaded the following four gene expression datasets from the Gene Expression Omnibus (GEO) database 1 : (1) GSE12682 (Si et al, 2009) comparing human kidney tissue between 29 healthy controls and 23 CKD samples, measured by the Affymetrix Human Genome U133A 2.0 Array (Affymetrix; Thermo Fisher Scientific, Waltham, MA, United States); (2) GSE12683 (Si et al, 2009) comparing Balb/c mouse kidney tissue between 10 healthy controls and 10 samples with AKI, measured by Affymetrix Mouse Genome 430A 2.0 Array; (3) GSE102513 (Vandenbussche et al, 2018) comparing CD-1 mouse kidney tissue between four healthy controls and four samples CKD induced by Tacrolimus (1 mg/kg/day for 28 days), measured by the Agilent-028005 SurePrint G3 Mouse GE 8x60K Microarray; and (4) GSE85957 (Pavkovic et al, 2014) comparing Rattus norvegicus (brown rat) kidney tissue samples between 19 healthy controls and 38 rats with kidney disease induced with 1 or 3 mg/kg cisplatin. In this last dataset, tissue was collected on days 3, 5, 8, and 26, and gene expression was measured using the Rat Genome 230 2.0 Array.…”
Section: Prediction Of Genes Associated With Aki or Ckdmentioning
confidence: 99%